Intergovernmental Fiscal Reform in China - Wingender, Philippe (Washington, D.C. : International Monetary Fund, 2018)
China is the most decentralized country in the world in terms of expenditures shares, with subnational governments responsible for 85 percent of government spending. Limited revenue autonomy and insufficient intergovernmental transfers have led to large unfunded mandates and a build-up of debt outside the budget. The government has recently announced an ambitious intergovernmental fiscal reform, which will increase the role of the central government. Comprehensive reform is needed to improve public service delivery, increase overall social spending levels and reduce regional disparities. Revenue reforms are also necessary to improve efficiency and reduce vulnerabilities from excessive subnational borrowing. These reforms are challenging, but are crucial so that the government can support China's continued development and prosperity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet